Strategi Peningkatan Target Angkutan Pupuk Dengan Optimalisasi Sistem Voyage Charter di PT Pupuk Indonesia Logistik - Nabila Putri, Imas Aulia; Amrullah, Romanda Annas; Pribadi, Teguh; Rakhman, Rizqi Aini (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the strategy to increase fertilizer transportation target by optimizing the voyage charter system at PT Pupuk Indonesia Logistik (PILOG). This system was chosen because of its flexibility in adjusting transportation needs based on cargo availability. The method used is a mix method with data collection techniques through observation, interviews, and questionnaires, and analyzed using the SWOT approach. The results of the study indicate that the company's main strength lies in regulatory support as a subsidiary of a BUMN and experience in fertilizer distribution. However, the limitations of its own fleet and dependence on third-party ship rentals are significant weaknesses. Great opportunities arise from the increasing demand for national fertilizer, but there are threats in the form of extreme weather and fluctuations in ship charter costs. The resulting strategies include establishing strategic partnerships, gradual investment in our own fleet, and optimizing the logistics system to reduce the risk of distribution disruptions. This research is expected to be a reference in making strategic decisions for companies to achieve efficiency and increase the volume of fertilizer transportation sustainably.